Neural Signals Related to Outcome Evaluation Are Stronger in CA1 than CA3 - Lee, Sung-Hyun; Huh, Namjung; Lee, Jong Won; Ghim, Jeong-Wook; Lee, Inah; Jung, Min W. (Frontiers in Neural Circuits, 2017)
We have shown previously that CA1 conveys significant neural signals necessary to update value of the chosen target, namely chosen value and reward signals. To better understand hippocampal neural processes related to valuation, we compared chosen value- and reward-related neural activity between the CA3 and CA1 regions. Single units were recorded with tetrodes from the dorsal CA3 and CA1 regions of rats performing a dynamic foraging task, and chosen value- and reward-related neural activity was estimated using a reinforcement learning model and multiple regression analyses. Neural signals for chosen value and reward converged in both CA3 and CA1 when a trial outcome was revealed. However, these neural signals were stronger in CA1 than CA3. Consequently, neural signals for reward prediction error and updated chosen value were stronger in CA1 than CA3. Together with our previous finding that CA1 conveys stronger value signals than the subiculum, our results raise the possibility that CA1 might play a particularly important role among hippocampal subregions in evaluating experienced events.